Enhancing Vocabulary Mastery Using Scrabble Game - Mbere, Maria Anastasia; Yumelking, Marselus; Balik, Lusiana Mariyeta (LPPPIPublishing, 2025)
Vocabulary is a collection of words or phrases that are understood in a particular language and used by humans to communicate in everyday life. The researcher saw that the vocabulary ability of Yapenthom 1 Junior High School students was still very minimal, therefore the researcher conducted a study aimed at increasing vocabulary in students. The researcher used the scrabble game method as a teaching tool to improve English vocabulary in students. Scrabble game is a game played by small groups to arrange letters into words so that this game can improve vocabulary in students. This study used a classroom action research method to collect data conducted in one class. The results of Classroom Action Research in cycle one with an mean score of 61.77%. In cycle two the mean score was 71.59% and in the third cycle with an mean score of 92.95% from the results of this study indicate that the Scrabble game media is suitable for use in learning English. Besides that the scrabble game changes the atmosphere of the class to be more active and greatly helps students in increasing English vocabulary.